1986
DOI: 10.1083/jcb.102.5.1576
|View full text |Cite
|
Sign up to set email alerts
|

Three types of low density lipoprotein receptor-deficient mutant have pleiotropic defects in the synthesis of N-linked, O-linked, and lipid-linked carbohydrate chains.

Abstract: Abstract. Biochemical, immunological, and genetic techniques were used to investigate the genetic defects in three types of low density lipoprotein (LDL) receptor-deficient hamster cells. The previously isolated ldlB, ldlC, and ldlD mutants all synthesized essentially normal amounts of a 125,000-D precursor form of the LDL receptor, but were unable to process this receptor to the mature form of 155,000 D. Instead, these mutants produced abnormally small, heterogeneous receptors that reached the cell surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
236
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(245 citation statements)
references
References 40 publications
9
236
0
Order By: Relevance
“…Mutations in Cog7 might affect glycosylation in the Golgi and so impair localisation of these glycoproteins at the cell surface, resulting in failure of ring constriction. CHO cells deficient for either Cog1 or Cog2 exhibit defects in Golgi-associated processing reactions for the synthesis of N-linked, O-linked carbohydrate chains of glycoproteins and also glycolipids (Kingsley et al, 1986). Consistent with a requirement for the COG complex in processing lipid-linked carbohydrate chains, an enrichment of the ganglioside G M1 could be visualised in telophase spermatocytes stained with fluorescent CTB in wild type but not in Cog7 mutants.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Mutations in Cog7 might affect glycosylation in the Golgi and so impair localisation of these glycoproteins at the cell surface, resulting in failure of ring constriction. CHO cells deficient for either Cog1 or Cog2 exhibit defects in Golgi-associated processing reactions for the synthesis of N-linked, O-linked carbohydrate chains of glycoproteins and also glycolipids (Kingsley et al, 1986). Consistent with a requirement for the COG complex in processing lipid-linked carbohydrate chains, an enrichment of the ganglioside G M1 could be visualised in telophase spermatocytes stained with fluorescent CTB in wild type but not in Cog7 mutants.…”
Section: Discussionmentioning
confidence: 77%
“…Loss of Cog7 prevents the accumulation of G M1 to the cleavage site and affects the pattern of glycoconjugates at the cleavage equatorial membrane COG subunit deficiencies are associated with defects in processing carbohydrate chains of both glycoproteins and glycolipids resulting in altered cell surface glycoconjugates (Kingsley et al, 1986;Oka et al, 2005;Peanne et al, 2011;Reddy and Krieger, 1989;Ungar et al, 2006;Wu et al, 2004). We thus asked whether mutations in Cog7 affected the pattern of glycoconjugates at the cleavage furrow.…”
Section: Mutations In Cog7 Disrupt Golgi Architecture and Function Inmentioning
confidence: 99%
“…Yeast mutants with defects in COG subunits have also been identified and characterized (8,(14)(15)(16)(17)(18). It has been proposed that COG may directly or indirectly play a role in resident Golgi proteins' transport to, retention at, or retrieval to appropriate sites, or that it might otherwise determine the Golgi's structure and͞or luminal environment without necessarily disrupting overall se-cretion or endocytosis (11). The relevance of COG for CDG was first illustrated in 2004 by Wu et al (19), who showed that the underlying cause in a case of CDG-II was a defect in Cog7.…”
mentioning
confidence: 99%
“…Recent studies (9,10) have further refined this model (see below). In Cog1-or Cog2-deficient Chinese hamster ovary (CHO) cell mutants, multiple Golgi cisternae are dilated (7), and there are pleiotropic defects in Golgi-associated reactions affecting virtually all N-, O-, and lipid-linked glycoconjugates (11). Recent studies have also shown that depletion of Cog5 in HeLa cells by RNA interference results in dilated Golgi cisternae and glycosylation defects (9), and that transient depletion of Cog3 can apparently result in the formation of Golgi-derived vesicles distributed throughout the cytoplasm (12).…”
mentioning
confidence: 99%
“…The Conserved Oligomeric Golgi (COG) complex orchestrates the recycling of medial-and cis-Golgi resident proteins by acting as a tether to connect COPI vesicles with cis-Golgi membranes [49]. COG defects lead to abnormal glycosylation [50] because of missorting of 6 glycosylation enzymes and sugar transporters [51]. Whereas multiple classes of glycosylation are impaired, COG-related disorders are usually identified by detection of underglycosylated serum transferrin just like defects of N-glycosylation.…”
Section: Localization Of Glycosyltransferasesmentioning
confidence: 99%